Tytuł profesora w pierwszych latach przemian ustrojowych Rzeczypospolitej Polskiej - Wojtczak, Krystyna (Studia Prawa Publicznego, 2020)
The political changes initiated in 1989 affected many sectors of the state’s activity, including higher education and science. In 1990, the Sejm passed two new Laws – on Higher Education, and on Academic Degrees and Title. The former placed greater emphasis than before on the freedom to conduct scientific research. With the second act, it finally abandoned the possibility provided for by the 1965 solutions of granting two different titles of professor, i.e., associate professor and full professor, by introducing one academic title – “professor”. For the purposes of evaluating and establishing the significance of the solutions adopted by the 1990 Law, this article presents the procedure and conditions for awarding the titles of professor provided for in the 1965 Law in the wording in force prior to its repeal in 1990, as well as those introduced set out in the 2003 Law and in force until its amendment in 2011. The replacement of the two titles of professor with a single academic title did not limit the range of proposals for changes introduced at that time. In the article, particular attention is devoted to these. The main trend in research comes down to: (1) how the degree and scope of regulations adopted in 1990 differed from earlier solutions, and (2) whether, in the context of the 2003 Law they were sufficient and served the quality of academic advancements well. It is only by basing research on previous findings in this respect that conclusions could be drawn as to the legal meaning and significance of conferring the title of professor in the years 1990–2011. This approach in achieving the purpose of the discussions was also important for another reason. It made it possible to emphasize the changes in terms of awarding the title of professor from the solutions in force during the Polish People’s Republic to the norms adopted in the initial years of the political transformation, as well as to the new regulations introduced in the more strongly established Republic of Poland. These were not the same solutions, and the Act of 1990 placed them in the group of liberal solutions.